Criteria for Drug Reimbursement Decision-Making: An Emerging Public Health Challenge in Bulgaria - Georgi Iskrov (Balkan Medical Journal, 2016)
Background: During times of fiscal austerity, means of reimbursement decision-making are of particular interest for public health theory and practice. Introduction of advanced health technologies, growing health expenditures and increased public scrutiny over drug reimbursement decisions have pushed governments to consider mechanisms that promote the use of effective health technologies, while constraining costs.